The prevalence and outcome of covid-19 smell problems at Kurdistan Iraq - Abdul-Hamid Ibrahim, Samar; Emin , Abdulkhaliq (Diyala Journal of Medicine, 2022)
Background: In December of 2019, a new form of coronavirus was discovered in Wuhan,China. Signs and symptoms of it include tiredness, cough, and fever . Another common symptom of this respiratory disease is the loss of smell. Objective: To find the frequency of anosmia in COVID-19 patients in our community in relation to other communities and to determine the clinical outcome of patients affected by COVID-19. Patients and Methods: This is a cross-sectional study at Kurdistan Iraq conducted during the period from January 2021-January 2022 .The 460 cases were admitted to quarantine centers 320 were positive for COVID 19 .The sample size is (260) cases of smell affection with proven COVID-19 disease. Results: The percentage of smell affection patients were 81% of the sample size, they were as follows, the percentage of bad odor smell was 9%, alteration of smell was 21% , partial loss of smell was 24% and complete loss of smell was 27%. The female percentage of all patients were 55 % while male percentage was 45% . Conclusion: Olfactory dysfunction is one of cardinal symptoms of COVID 19 disease.Females are slightly more affected than males with olfactory dysfunction. 4 th and 5th decades patients are more affected with bad odor and alteration of smell while. partial loss and complete loss of smell happened within 6 th decade patient mostly.